Personality Competence of Islamic Religion Subject Teachers in the Development of the Al-karimah Character - Ridhwan Latuapo (STAI Hubbulwathan Duri, 2023)
This study departs from the researchers' anxiety over the importance of teacher personality competence in fostering student morals. The purpose of this study was to describe the Personality Competence of Islamic Religion Subject Teachers in the development of al-karimah morality in students. This study uses a qualitative approach, with procedures for observation, interviews, and documentation. The results of this study indicate that, broadly speaking, the personality competence of Islamic religious teachers at Madrasah Tsanawiyah is outstanding. This can be seen from the example teachers of Islamic religious subjects played in their school and community activities. For example, teachers of Islamic religious subjects often show personalities in accordance with religious norms, legal norms, and social norms. However, some teachers of Islamic religious subjects still are not optimal in controlling emotions and speaking words. The contribution of the personality competence of teachers of Islamic religious subjects in fostering the morals of students, through several forms, namely authority, teacher speaking morals, teacher socialising morals, teacher dress morals, and teacher respect for all the rules that apply in schools All of this is done by building internal awareness a strong self that is reflected in attitudes, actions and deeds.